Make Money, Not War: A Brief Critique of Sun Tzu's The Art of War - McCormick, Blaine (Journal of business ethics, 2001)
Sun Tzu's text of The Art of War remains a bestsellingand oft-referenced practioner's book. However, its generalizabilityto the current business environment is questionable. This reviewexamines two central tenets of the book – warfare anddeception – and critiques their relevance in lightof current business practice.